1983
DOI: 10.1063/1.94400
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of WSix/GaAs Schottky contacts

Abstract: The Schottky diode characteristics of WSix contacts on n-type GaAs have been investigated and correlated to the film stress in WSix and crystallographic properties of the film. Experimental results show that (1) the high-temperature stability of WSix/GaAs Schottky diode characteristics depends significantly on Si content; (2) WSix/GaAs contacts exhibit very high-temperature-stable Schottky diode characteristics at Si content around 0.60, and at this Si content no metallurgical interactions between WSix and GaA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The thermal stability of TiN [10] and MoSi 2 [11] contacts to GaAs has also been investigated, but they were found to be unstable contacts for annealing temperatures higher than 700°C and 500°C, respectively. _The degradation of these contacts at high temperatures was believed to be connected to the interdiffusion of GaAs and the contact materials at the interface [8,11]. This explanation, however, does not seem to be applicable to the W/GaAs contact studied by Matsumoto et al The excellent electrical behavior of the W/GaAs diode after annealing at 950°C observed by Matsumoto et al might be the result of the formation of a uniform layer of -3-a W-GaAs intermetallic compound at the W/GaAs interface.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal stability of TiN [10] and MoSi 2 [11] contacts to GaAs has also been investigated, but they were found to be unstable contacts for annealing temperatures higher than 700°C and 500°C, respectively. _The degradation of these contacts at high temperatures was believed to be connected to the interdiffusion of GaAs and the contact materials at the interface [8,11]. This explanation, however, does not seem to be applicable to the W/GaAs contact studied by Matsumoto et al The excellent electrical behavior of the W/GaAs diode after annealing at 950°C observed by Matsumoto et al might be the result of the formation of a uniform layer of -3-a W-GaAs intermetallic compound at the W/GaAs interface.…”
Section: Introductionmentioning
confidence: 99%
“…MoF6 + 2Sill4 --~ MoSi2 + 6HF + H2 [1] MoF6 + 3Sill4 --* MoSi2 + SiH3F + 5HF + 2H2 [2] MoF6 + 3Sill4 -~ MoSi2 + SiH2F2 + 4HF + 3H2 [3] MoF6 + 3Sill4 --~ MoSi2 + SiHF3 + 3HF + 4H2 [4] MoF6 + 3Sill4 --~ MoSi2 + SiF4 + 2HF + 5H2 [5] The reactions are listed in order of increasing thermochemical driving force. The Gibbs free energies for these reactions are plotted as a function of temperature in Fig.…”
Section: Reaction Chemistrymentioning
confidence: 99%
“…Since excess As is required at the interface to form anion clusters, this approach could be considered as coincident with the defect approach in which Asaa antisites are assumed to be dominant. 42 Freeouf 6. Hence, the electrical characteristics of these nitride contacts can remain relatively unchanged or even improved after annealing.…”
Section: Effective Work Function Modelmentioning
confidence: 99%